Giant Congenital Sialolipoma of Parotid Gland with Parapharyngeal Extension - Erdağ, Taner-Kemal (Iran J Otorhinolaryngol, 2019)
INTRODUCTION: Sialolipoma is an extremely rare salivary gland tumor characterized by a well circumscribed mass composed of glandular tissue and mature adipose elements. Herein our aim was to present the fifth case of congenital sialolipoma, which was firstly followed up as a parotid gland hemangioma, and underline the fact that sialolipomas should be kept in mind in the differential diagnosis of congenital parotid gland masses. CASE REPORT: A 10-month old male presented with a left-sided huge neck mass which progressed after birth. Radiologic examination revealed a tumor originating from the parotid gland filling the parapharyngeal space. Histopathologic examination of an incisional biopsy was consistent with sialolipoma. A total parotidectomy with preservation of the facial nerve was performed at the age of 1 year. The postoperative recovery was uneventful with normal facial nerve function. There was no recurrence at the 24-month follow-up. CONCLUSION: Although it is a very rare benign tumor, congenital sialolipoma should be kept in mind in the differential diagnosis of congenital parotid mass.